Survei Orientasi dan Perilaku Berkunjung Mahasiswa Baru ke Perpustakaan Menggunakan Teori Uses and Gratifications - Marsih, Leni; Andres, Monalisa Fitri; Saputra, Andi (Media Pustakawan, 2025)
After the COVID-19 pandemic, students' behavior and habits in lectures have changed, which has an impact on visits to the library. This research aims to identify areas of improvement in library services as user behavior changes, so that libraries remain relevant and maximal in improving academic quality in universities. A quantitative approach is used with data collection through questionnaires. The questionnaire consisted of demographic data of respondents, the behavior of new students' visits to the library, their orientation and motivation for visiting, and expectations for the library's contribution in supporting the success of the study. The instruments are structured based on the theory of Uses and Gratifications. The results of the study showed that there was a shift in the orientation of library visitors, although it was not too significant. Conventional services such as borrowing and returning books and user guidance tend to decline. Meanwhile, the need for new services that are recreative in nature is increasing. Overall, the study concludes that the majority of students expect libraries to be comfortable places to study, read, and rest.